Effect of Dietary Protein on Egg Production and Immunity Responses of Laying Hens During Peak Production Period - Bunchasak, Chaiyapoom; Poosuwan, Kanokan; Nukraew, Rattana; Markvichitr, Kanchana; Choothesa, Apassara (International Journal of Poultry Science, 2005)
The study was completely randomized design. Six hundred and seventy two commercial laying hens (Babcock B-308) from 21 to 33 weeks of age were used. The hens were divided into 3 groups; each group consisted with 6 replications of sixteen layers each, and then two hens were kept in a multiple-cage located in evaporative cooling house system. Feed and water were offered ad libitum. According to the experimental groups, 3 levels of dietary protein (14, 16 and 18% CP) with similar energy content (2,750 ME kcal/kg) were given to the hens in order to investigate effects of dietary protein on their production performances, liver triglyceride, serum non-esterified fatty acid (NEFA) and immunity responses during peak production period. The results showed that hens received 14% CP diet had significantly poorer in production performances than the 16 and 18% CP groups. Liver weight of hens fed 14% CP diet was smaller than those of 16 and 18% CP diets (P< 0.05). However, the protein conversion ration was significantly improved as decrease of protein consumption (P< 0.01), while feed intake was not significantly affected by dietary protein levels. There were tendencies of increase of liver triglyceride and NEFA due to high protein consumption. For the immunological aspect, Newcastle disease (ND) titre of hens fed 18% CP diet was significantly higher than those of hens fed 16 and 18% CP diets (P< 0.05). Except alpha-globulin and ratio of albumin : globulin that tended to decline, all serum protein fractions and serum total protein were tended to increase as protein levels increased. Spleen size was not affected by dietary protein levels.